2017
DOI: 10.2105/ajph.2017.303661
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Care Receipt and Self-Rated Oral Health for Diverse Asian American Subgroups in New York City

Abstract: Nonreceipt of annual oral health examinations and poor self-rated oral health were common across Asian American subgroups. Facilitating dental insurance sign-up and providing in-language services may improve oral health care access and ultimately oral health among Asian American immigrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 3 publications
2
16
0
Order By: Relevance
“…This increase in unmet needs due to the cost of services occurred especially in the lowest income quintiles. Although there are few studies accounting for place of birth on the inequalities in the use of dental services, and even fewer including some of the immigrant groups considered in our study, their findings are consistently with ours showing lower use of dental services in immigrants from Africa and Asia [19,29,36,37]. These studies suggested lack of dental insurance, the cost of services and lower income as possible explanations for these inequalities.…”
Section: Discussionsupporting
confidence: 89%
“…This increase in unmet needs due to the cost of services occurred especially in the lowest income quintiles. Although there are few studies accounting for place of birth on the inequalities in the use of dental services, and even fewer including some of the immigrant groups considered in our study, their findings are consistently with ours showing lower use of dental services in immigrants from Africa and Asia [19,29,36,37]. These studies suggested lack of dental insurance, the cost of services and lower income as possible explanations for these inequalities.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, factors that contributed to the lack of annual oral health examinations included poor English fluency, low educational attainment, and lack of dental insurance. Lack of English proficiency compared with English fluency was associated with a 2‐fold increase of not receiving oral health examinations . Similarly, in another study of older Asian Americans, older adults with limited English fluency were 3.5 more times likely to lack dental health insurance.…”
Section: Discussionmentioning
confidence: 89%
“…Chinese older adults face barriers that may contribute to our findings. For example, in a sample of 1288 Asian Americans living in New York City, 41.5% reported not receiving annual oral health examinations . Furthermore, factors that contributed to the lack of annual oral health examinations included poor English fluency, low educational attainment, and lack of dental insurance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey was community-based and was administered in-language among individuals self-identifying as Asian American living in the NYC metropolitan region between the years 2013 and 2015, with most surveys completed in 2014 (69.6%) and 2015 (28.2%). Survey methods have been previously described [26]. …”
Section: Methodsmentioning
confidence: 99%